Double-Phase Elliptic Equations with Nonlinear Sources Existence and Uniqueness of the Weak Solution (Journal of Nonlinear Modeling and Analysis, 2025)
In our work, our objective is to prove the existence and uniquenessof a weak solution to a class of nonlinear degenerate elliptic $(p, q)$-Laplacianproblem with Dirichlet-type boundary condition by giving $L^ ∞$ data. Theprincipal technique utilized here is the variational method alongside the theoryof Orlicz spaces and Minty-Browder theorem.